The Comparison of Urinary Cadmium (UCd) and Urinary Lead (UPb) between 2007 and 2015 in a Population Living in a Zinc Contaminated Area: DOI: 10.32526/ennrj.17.2.2019.12 - Chaiwong, Sanhawat; Chanthanao, Wikrom; Loeskhampom, Pramote; Wiwatanadate, Phongtape; Sthiannopkao, Suthipong (Environment and Natural Resources Journal, 2018)
This paper compares urinary cadmium (UCd) and lead (UPb) between 2007 and 2015 in a population living in an area of zinc contamination and classified in terms of year, subdistrict, gender and gender broken down by age. A total of 441 participants from zinc contaminated areas gave urine samples in 2007 and again in 2015 for analysis of cadmium and lead concentrations. Urine was divided into 2 parts for: 1) cadmium and lead analysis by ICP-MS and 2) urinary creatinine (Cr) measurement by the modified Jaffe’s reaction method. The statistical analysis includes mean, frequency and percentage, paired t-test and ANOVA. The results show a statistically significant decrease in the urinary concentrations of cadmium and lead in 2015 compared to 2007 for: 1) all subdistricts, 2) year, 3) age group, 4) gender and 5) gender by age. The reduction was greater in gender by age of females than in that of males, but this was not statistically significant. The conclusion illustrates that UCd and UPb in terms of years, sub districts (Prathadpadeang, Mae Tao and Mae Ku), gender, and gender by age (a cross tabulation of gender and age) show a statistically significant decrease from 2007 to 2015.